2006
DOI: 10.1111/j.1365-2141.2006.06072.x
|View full text |Cite
|
Sign up to set email alerts
|

Joe Burchenal and the birth of combination chemotherapy

Abstract: SummaryWhen Joe Burchenal started studying medicine at the University of Pennsylvania in 1934, antibiotics had not been discovered and the survival of patients diagnosed with acute leukaemia was <4 months. By the time he retired in 1983, 58% of children with acute lymphoblastic leukaemia survived 5 years with the majority being cured of their disease. His early work in infectious diseases and antimicrobials equipped him well, both clinically and scientifically. The approach to developing antibiotics to conquer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The folate analog methotrexate (MTX) and the thio-substituted purine analog 6-mercaptopurine (6MP) became pioneering anticancer agents more than half a century ago, when first Farber et al1 and then Burchenal2,3 demonstrated that such drugs can induce temporary remissions in childhood leukemia. Soon cure became the goal,4,5 and through a series of trials it was shown that the chance of long-term remission of childhood acute lymphoblastic leukemia (ALL) was significantly improved, when patients received several years of postremission maintenance therapy with daily 6MP and weekly MTX 4–8.…”
mentioning
confidence: 99%
“…The folate analog methotrexate (MTX) and the thio-substituted purine analog 6-mercaptopurine (6MP) became pioneering anticancer agents more than half a century ago, when first Farber et al1 and then Burchenal2,3 demonstrated that such drugs can induce temporary remissions in childhood leukemia. Soon cure became the goal,4,5 and through a series of trials it was shown that the chance of long-term remission of childhood acute lymphoblastic leukemia (ALL) was significantly improved, when patients received several years of postremission maintenance therapy with daily 6MP and weekly MTX 4–8.…”
mentioning
confidence: 99%
“…Although small successes were seen with this chemotherapy regimen, these researchers were encouraged to experiment with other combinatorial chemotherapies for the treatment of solid tumors. Dr. Burchenal and Herbert Oettengen, along with 14 other scientists, received the 1972 Albert Lasker Award for Medical Research for their contributions to the treatment of Burkitt lymphoma (2,3).…”
mentioning
confidence: 99%